Determinants of glucose control among elderly diabetics in Kulim. - Rahmah, MA; Noraishah, J (Penerbit UKM, 2011)
Globally, the prevalence of diabetes mellitus and the average life expectancy is on the rise. As diabetes mellitus is commonly associated with old age, it is very important to ensure good glucose control to reduce complications and improve quality of life. A cross sectional study was conducted among elderly diabetics in Kulim with the aim to determine the prevalence of glucose control and its associated factors. Three hundred and twenty nine respondents were chosen through stratified random sampling in all the seven health clinics in Kulim. Respondents were interviewed personally using a structured questionnaire. HbA1c level of 6.5% and below was considered as good glucose control. Prevalence of good glucose control was 22.5%. Being male (Adjusted prevalence odds ratio, APOR = 1.75, 95% CI: 1.02-3.00), age of 70 years and above (APOR = 2.48, 95% CI: 1.40-4.39) and duration of diabetes less than five years (APOR = 2.10, 95% CI:1.21-3.64 ) were found to have significant association with good glucose control. As a conclusion, this study showed that the low prevalence of good glucose control was determined by gender, age and duration of illness.